An AI-Driven Framework for Optimizing Business Intelligence across Organizational Hierarchies - Thaher, Mohammed Shaban (Engineering, Technology & Applied Science Research, 2025)
In today’s global trade landscape, Artificial Intelligence (AI) significantly enhances productivity and transforms business processes across sectors. This research investigates the role of business intelligence in improving service delivery within corporate entities. By applying Deming’s methodology, strategies to optimize decision-making processes are identified, and hidden insights are revealed through advanced data analysis techniques. A Data Flow Diagram (DFD) illustrates the development stages and system implementation, offering practical guidance for general managers. The findings provide actionable insights that enhance efficiency and decision-making in organizational contexts.